Elderly Quality of Life and Its Predictors in Chronic Disease Management Program: Indonesian Version of WHOQOL-BREF and WHOQOL-OLD - Lionthina, Melly; Wiwaha, Guswan; Gondodiputro, Sharon; Sukandar, Hadyana; Arya, Insi Farida Desy; Sunjaya, Deni K. (Majalah Kedokteran Bandung, 2020)
Indonesia is currently experiencing increasing proportion of older population, which also increases the prevalence of chronic diseases that may decrease the quality of life (QoL). The Indonesian Social Security Agency develops a program to control chronic diseases, which is referred to as the Chronic Disease Management Program (Program Pengelolaan Penyakit Kronis, PROLANIS) for the National Health Insurance participants. Its goals is to control chronic diseases in order to improve participants’ QoL. To evaluate the QoL of the elderly, the World Health Organization (WHO) has developed two questionnaires, namely WHOQOL-BREF and WHOQOL-OLD. The objective of this study was to analyze the differences in the QoL of the elderly between PROLANIS and non-PROLANIS participants using the Indonesian-verson of WHOQOL-BREF and WHOQOL-OLD as well as the QoL predictors. A cross-sectional study was carried out to 84 elderly PROLANIS participants (n=42) and non-PROLANIS participants (n=42). Respondents were sampled consecutively from 6 public health health centers (Pusat Kesehatan Masyarakat, Puskesmas) in Bangka District, Indonesia in 2018. Mann Whitney test or the unpaired T test were used to statistically analyze the difference between the two groups. A multiple linear regression test was then carried out to determine the predictors of the QoL. This study discovered that no difference was observed in the QoL of the elderly between PROLANIS and non-PROLANIS participants. Disease status and depression were the predictors of the QoL. Therefore, PROLANIS has not been proven to be able to improve the QoL of the elderly. Kualitas Hidup Lanjut Usia dan Prediktornya pada Program Pengelolaan Penyakit Kronis: Versi Indonesia dari WHOQOL-BREF dan WHOQOL-OLD Peningkatan proporsi penduduk lanjut usia (lansia) di Indonesia meningkatkan prevalensi penyakit kronis sehingga dapat menyebabkan penurunan kualitas hidup. Badan Penyelenggara Jaminan Sosial mengembangkan Program Pengelolaan Penyakit Kronis (PROLANIS) bagi peserta Jaminan Kesehatan Nasional dengan tujuan agar penyakit kronis tersebut terkontrol dan lansia dapat hidup berkualitas. World Health Organization (WHO) mengembangkan instrumen untuk mengukur kualitas hidup, yaitu WHOQOL-BREF dan WHOQOL-OLD. Penelitian ini bertujuan menganalisis adanya perbedaan kualitas hidup lanjut usia antara bukan peserta PROLANIS dan peserta PROLANIS menggunakan kuesioner WHOQOL-BREF dan WHOQOL-OLD versi Bahasa Indonesia dan faktor yang berpengaruh. Penelitian potong lintang dilakukan pada 84 lansia yang terbagi menjadi 2 grup masing-masing 42 responden, yaitu bukan peserta PROLANIS danpeserta PROLANIS. Responden berasal dari 6 Puskesmas di Kabupaten Bangka Provinsi Bangka Belitung Indonesia pada tahun 2018 yang dipilih sesuai kriteria inklusi dan dengan metode consecutive sampling. Data yang terkumpul dilakukan analisis menggunakan Uji Mann Whitney atau uji T tidak berpasangan. Uji regresi linier multipel dilakukan untuk menentukan prediktor dari kualitas hidup. Hasil penelitian menunjukkan bahwa tidak ada perbedaan kualitas hidup lansia antara bukan peserta PROLANIS dan peserta PROLANIS. Status penyakit dan depresi merupakan prediktor kualitas hidup. Simpulan, PROLANIS belum terbukti dapat meningkatkan kualitas hidup lansia.